A man's reach - Andersen, Elmer L., 1909-2004 (Minnesota., 2000)
"Elmer L. Andersen has been described as Minnesota's leading citizen. As a Minnesota state senator, he pioneered progressive legislation in the areas of civil rights, special education and welfare, mental health care, and metropolitan governance. His term as Minnesota's governor in the early 1960s was marked by the founding of Southwest State University and the establishment of several state parks, which, along with his role in the creation of Voyageurs National Park, gained him a reputation as one of the region's most important environmentalists. He built a small adhesives business, H.B. Fuller Company, into a world leader, and created a publishing empire from one weekly newspaper. His philanthropic legacy has significantly contributed to educational and cultural institutions throughout the state."--Jacket